2018
DOI: 10.1002/ijc.31917
|View full text |Cite
|
Sign up to set email alerts
|

Association of breast cancer risk with polymorphisms in genes involved in the metabolism of xenobiotics and interaction with tobacco smoking: A gene‐set analysis

Abstract: Single nucleotide polymorphisms (SNPs) in genes involved in xenobiotics metabolism (XM) are suspected to play a role in breast cancer risk. However, previous findings based on a SNP by SNP approach need to be replicated taking into account the combined effects of multiple SNPs. We used a gene‐set analysis method to study the association between breast cancer risk and genetic variation in XM genes (seen as a set of SNPs) and in the XM pathway (seen as a set of genes). We also studied the interaction between var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“… No. Gene Symbol Association with Gender Association with Smoking [ 61 ] 1 [ 62 ] [ 113 ] 2 [ 114 ] 3 [ 115 ] 4 [ 116 ] 5 [ 117 ] 5 [ 118 ] 5 [ 119 ] [ 120 ] Upregulated genes 1 CPT1A no no no no no no no no no no 2 GGT1 no no no no no no no no no no 3 …”
Section: Abdominal Aorta Aneurysm and Control Groups Constructionmentioning
confidence: 99%
“… No. Gene Symbol Association with Gender Association with Smoking [ 61 ] 1 [ 62 ] [ 113 ] 2 [ 114 ] 3 [ 115 ] 4 [ 116 ] 5 [ 117 ] 5 [ 118 ] 5 [ 119 ] [ 120 ] Upregulated genes 1 CPT1A no no no no no no no no no no 2 GGT1 no no no no no no no no no no 3 …”
Section: Abdominal Aorta Aneurysm and Control Groups Constructionmentioning
confidence: 99%
“…A large pooled analysis showed that heavy smokers had higher estrogen and androgen levels, which may also contribute to cancer risk [102]. Single-nucleotide variants in genes involved in xenobiotics metabolism, which detoxify environmental pollutants such as those contained in tobacco smoke, may have a role in breast carcinogenesis [103].…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Some studies suggested that men were happier and lower levels of psychological stress when doing the housework such as cooking might make them nd the meaning and purpose of life [14,36]. In addition, most men's drinking and smoking behavior will affect the secretion and metabolism of hormone [37,38], thus overshadowing the effect of housework on human metabolism. The underlying mechanism between male housework and metabolism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%